Learning Methods According to Modern Obaidat - Adinda Roisatul Fawziyah (Jurnal Impresi Indonesia, 2024)
Method is a way used to achieve certain goals. This method greatly affects students in receiving the knowledge delivered. The purpose of this research is to find out the learning method according to Obaidat. To achieve the research objectives, the author uses the type of library research by using written materials that have been published in the form of books and journals.  There are 11 learning methods according to Obaidat, namely, lecture method, discussion method, brainstorming method, story method, problem solving method, project method, assignment method, field trip method, survey method, concept map method, and play while learning method. Remedial learning with the problem solving method is learning that is dominated by student activeness, so the success in overcoming student difficulties is higher than remedial learning with conventional methods that involve less student activeness. From the many existing learning methods, it can be concluded that students can use any method, as long as learning can take place optimally and students can understand the material presented. With the right learning method, it can encourage the growth of students' enjoyment of lessons, foster and increase motivation in doing assignments, make it easier to understand lessons, thus enabling students to achieve better learning outcomes.